Recommended species for urban tree planting in Monteria, Colombia (REVISTA NODO, 2014)
The article is part of the research on Monteria´s urban public space vegetation. It presents a series of native species suitable for urban tree planting in Monteria that contribute to the Main Ecological Structure and, at the same time, deliver aesthetic value to the urban environment while conveying a sense of identity to the city in regards to its native plant life. For the same reasons, it suggests other species that are currently under different threats in order to promote its conservation, provides a listing of indigenous species requiring special management, and offers some tips and recommendations to take into account to succeed at a tree planting strategy, analyzing thoroughly the overall state of Monteria´s ecological population of trees.
Keywords: Urban ecology; native plant life; public space